Influence of impurities on the performances of HIPS recycled from Waste Electric and Electronic Equipment (WEEE). (October 2016) - Perrin, Didier; Mantaux, Olivier; Ienny, Patrick; Léger, Romain; Dumon, Michel; Lopez-Cuesta, José-Marie
Highlights: Determination of maximal impurities tolerance from ABS, PP, PS into HIPS is observed. A new method based on ESEM in-situ tensile tests to view the damage is carried out. The problem of immiscibility of recycled polymer blend from sorting is tackled. Abstract: In order to produce a high quality recycled material from real deposits of electric and electronic equipment, the rate of impurities in different blended grades of reclaimed materials has to be reduced. Setting up industrial recycling procedures requires to deal with the main types of polymers presents in WEEE (Waste Electric and Electronic Equipment), particularly High Impact Polystyrene (HIPS) as well as other styrenic polymers such as Acrylonitrile-Butadiene-Styrene (ABS), Polystyrene (PS) but also polyolefin which are present into WEEE deposit as Polypropylene (PP). The production of a substantial quantity of recycled materials implies to improve and master the compatibility of different HIPS grades. The influence of polymeric impurities has to be studied since automatic sorting techniques are not able to remove completely these fractions. Investigation of the influence of minor ABS, PS and PP polymer fractions as impurities has been done on microstructure and mechanical properties of HIPS using environmental scanning electron microscopy (ESEM) in order to determine the maximum tolerated rate for each of them into HIPS after sorting and recycling operations.